Dehidrasi N-Butanol menjadi senyawa butena pada katalis molecular sieve 13X dalam reaktor unggun tetap - Melia Laniwati Gunawan; Hendrik Susanto (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2007)
One of the ways of producing butene compounds without relying on non-renewable resources involves the dehydration of n-butanol with the aid of acid catalysts. The dehydration of n butanol on molecular sieve 13 X catalyst has been undertaken in afvced bed, vertical glass pipe isothermal reactor. Reaction temperatures were varied between 300-450 °C. Reaction products were analyzed using a Gas Chromatograph (GC). The n-butanol dehydration was observed to have a reaction order of 1.95 with respect to n-butanol partial pressure, with an activation energy of 89.4 kJ/mol and an Arrhenius constant of 7.99 x 106 .To determine the effect of operating parameters (feed temperature, n-butanol flowrate, n-butanol to nitrogen feed ratio, and catalyst particle diameter), a simulation was undertaken based on the fvced bed, non adiabatic and non-isothermal reactor model. The reactor model used in the simulation was a 2- dimensional heterogeneous reactor. The validated model coefficient of correlation against the experimental data was very good, namely 0.98. Simulation results indicate that the increase in n-butanol concentration and feed temperature increase the conversion. Increase in catalyst particle diameter and feed flowrate decrease the conversion. The dehydration of n-butanol to butene is a mildly exothermic reaction. Therefore, to maintain an isothermal reaction condition, the reactor wall temperature may not exceed 10 °C below the feed temperature.Keywords: n-butanol dehydration, molecular sieve 13 X, simulation, fixed bed, kineticAbstrakSalah satu cara untuk mendapatkan senyawa butena tanpa mengandalkan sumber daya tak terbarukan adalah melalui dehidrasi n-butanol dengan bantuan katalis asam. Dehidrasi n butanol pada katalis molecular sieve 13 X dilakukan di dalam reaktor unggun tetap terbuat dari pipa gelas tegak secara isotermal. Temperatur reaksi divariasikan antara 300 - 450